Intertrip consistency in hunting behavior improves foraging success and efficiency in a marine top predator - Speakman, Cassie N. (Ecol Evol, 2021)
Substantial variation in foraging strategies can exist within populations, even those typically regarded as generalists. Specializations arise from the consistent exploitation of a narrow behavioral, spatial or dietary niche over time, which may reduce intraspecific competition and influence adaptability to environmental change. However, few studies have investigated whether behavioral consistency confers benefits at the individual and/or population level. While still recovering from commercial sealing overexploitation, Australian fur seals (AUFS; Arctocephalus pusillus doriferus) represent the largest marine predator biomass in south‐eastern Australia. During lactation, female AUFS adopt a central‐place foraging strategy and are, thus, vulnerable to changes in prey availability. The present study investigated the population‐level repeatability and individual consistency in foraging behavior of 34 lactating female AUFS at a south‐east Australian breeding colony between 2006 and 2019. Additionally, the influence of individual‐level behavioral consistency on indices of foraging success and efficiency during benthic diving was determined. Low to moderate population‐level repeatability was observed across foraging behaviors, with the greatest repeatability in the mean bearing and modal dive depth. Individual‐level consistency was greatest for the proportion of benthic diving, total distance travelled, and trip duration. Indices of benthic foraging success and efficiency were positively influenced by consistency in the proportion of benthic diving, trip duration and dive rate but not influenced by consistency in bearing to most distal point, dive depth or foraging site fidelity. The results of the present study provide evidence of the benefits of consistency for individuals, which may have flow‐on effects at the population level.